The Effect of the Combination of Probiotics and Heavy Metals From Various Aspects in Humans: A Systematic Review of Clinical Trial Studies - Atieh Darbandi; Tahereh Navidifar; Maryam Koupaei; Roghayeh Afifirad; Reyhaneh Amin Nezhad; Amir Emamie; Malihe Talebi; Maryam Kakanj (Health Science Reports)
ABSTRACT Background and Aims Probiotics usually have beneficial effects on the absorption of trace elements and detoxification of toxic metals in human. Hence, the aim of the systematic review was to evaluate various aspects of the effect of the combination of probiotics and heavy metals in human clinical trial studies. Methods Nine databases were searched for clinical trials up to June 2024 investigating probiotics for heavy metal exposure in humans. Two reviewers independently screened records and extracted data on study characteristics, interventions, outcomes, and results. Risk of bias was assessed. Results The analysis included 31 clinical trials with a total of 4,611 participants, focusing on the effects of probiotics, prebiotics, and synbiotics. Among the trials, 23 investigated probiotics, five looked at prebiotics, and three explored synbiotics, with probiotic doses ranging from 107 to 2.5 × 1010 CFU/day. Results indicated that probiotics combined with zinc significantly reduced the time to resolution of vomiting and diarrhea compared to zinc alone, improved the treatment efficacy of antibiotic‐associated diarrhea linked to pneumonia, and shortened hospital stays relative to probiotics alone. Probiotics did not show significant effects on blood parameters compared to placebo; however, prebiotic galactooligosaccharides enhanced iron absorption in women and children. The addition of probiotics to bismuth quadruple therapy did not improve Helicobacter pylori eradication rates but reduced side effects like diarrhea and vomiting. One trial reported a decrease in toxic metal levels in pregnant women due to probiotics, but no similar effects were observed in children. Conclusions Probiotics are one of the new methods employed to improve or eliminate the adverse effects of heavy metals in the body. Although many studies have investigated the effects of probiotics on heavy metals, there is still a need for more in‐depth and extensive studies.